Perancangan User Experience Aplikasi Mobile Fitur Send Your Waste menggunakan Pendekatan Design Thinking (Studi Kasus: Waste4Change) - Ramadhani Imam Khoiri; Agi Putra Kharisma; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Waste4Change is a company that focuses on solving waste problems, starting from the education process to managing it so that waste does not go into landfills. Waste4Change has a feature, namely SYW (Send Your Waste) which functions to manage several types of waste so that they are not disposed of directly into landfills. Waste4Change wants to make an application from the Send Your Waste feature that can make it easier for users to use the system with a good flow. From these problems, an application was designed from the Send Your Waste feature to make it easier for users to send their waste to Waste4Change. This study uses a Design Thinking approach. The evaluation stage is carried out by testing the design results using usability testing with 5 respondents who produce a score of 85% on effectiveness testing, 0.094 goals/second on efficiency testing, and 85.5 on user satisfaction testing. The next test was the User Experience Question (UEQ) which was tested twice. The first test is with 5 respondents who get excellent results on all scales and the second test is with 15 respondents who get excellent results in almost all aspects, except on the perspicuity scale.